A coding optimized polarization conversion metasurface in broadband and wide‐angle. Issue 5 (29th November 2019) - Han, Jiangfeng; Cao, Xiangyu; Gao, Jun; Yu, Huicun; Zhang, Zhao; Li, Sijia
Abstract: In this article, a coding optimized metasurface is proposed for linear polarization conversion in broadband and wide‐angle. Using an improved coding method, the geometry of the metallic structure and the size of the unit cell are encoded with a code sequence. The code sequence is optimized by genetic algorithm, considering bandwidth, efficiency, and angular stability. In this way, a coding optimized metasurface was obtained for polarization conversion in broadband and wide‐angle. It can convert linear polarized incidence to its orthogonal polarized reflection in 8 to 18.9 GHz and 0° to 45°, with the polarization conversion ratio larger than 80%. Both simulated and measured results demonstrated the effectiveness of the proposed metasurface. Hence, our method offers an effective strategy to design high‐performance polarization conversion metasurfaces.